Efficiency criteria for environmental model quality assessment: A review and its application to wastewater treatment. (June 2015) - Hauduc, H.; Neumann, M.B.; Muschalla, D.; Gamerith, V.; Gillot, S.; Vanrolleghem, P.A.
Abstract: In various cases in environmental modeling, modelers need to account for multiple variables and multiple objectives in systems with many processes occurring at different time scales. To assist the modeler to choose a relevant pool of efficiency criteria, a method is proposed to identify dissimilar criteria. A total of 30 efficiency criteria used in environmental modeling are critically reviewed and classified into six groups according to different modeling objectives. After accounting for equivalence of functional form 18 criteria remain for further analysis. To quantify the dissimilarity for the remaining criteria a methodology based on the ratio of shared parameter sets in regions of good performance is proposed. Then, for a wastewater treatment plant case-study the dissimilarity of efficiency criteria is analyzed as a function of target variables and operating conditions. Graphical abstract: Highlights: 30 efficiency criteria of model quality in environmental sciences are reviewed. After studying equivalence of functional form 18 efficiency criteria remain. A methodology is proposed to quantify dissimilarity between remaining criteria. The methodology is applied to a wastewater treatment plant case study. Dissimilarity is assessed as a function of target variables and operating conditions.